DESAIN MEDIA FILTER PASIR SILIKA DAN FILTER KARBON AKTIF SEBAGAI TEKNOLOGI PENGOLAHAN AIR TANAH TERCEMAR DI SEKITAR LAHAN BEKAS TPA KEPUTIH - Alifa Al Nawiswary; Bieby Voijant Tangahu (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2022)
The use of open dumping methods in Indonesia landfills does not have adequate environmental protection facilities. The by-products of landfilling activities, namely leachate gas and water, will accumulate and cause pollution at some time, either during the management process or after activity. Groundwater quality around the former Keputih landfill area has been polluted. This groundwater has not met the quality standards of Permenkes RI No. 32 of 2017 concerning Environmental Health Quality Standards and Water Health Requirements for Sanitary Hygiene Purposes, Swimming Pools, Solus Per Aqua, and Public Baths. The polluted parameters include: TDS (1630 mg/L), turbidity (29.4 NTU), color (173.7 PtCo Units), Fe (2.01 mg/L), Mn (0.76 mg/L), total hardness (621.43 mg/L), detergent (1.27 mg/L) and organic matter (11.4 mg/L). one alternative remediation technology for groundwater contaminated with leachate can use silica sand filter media and activated carbon filters. The selection of alternative remediation technology refers to scoring matrix with the value of maintenance and treatment aspects, capital investment, processing efficiency, operational costs, groundwater recovery time and expert labor requirements. The initial planning of this remediation technology was carried out by determining the treatment capacity with a projected clean water demand of 120% of the average water demand. The remediation technology designed has a capacity of 8,930 L/day. The planned technology design is a shallow well pump, silica sand filter unit, activated carbon filter unit and water reservoir equipped with a backwash pump. The remediation process is carried out in 3 cycles per day. The time of each cycle is 8 hours, with a remediation process time of 80 minutes. The discharge that flows per cycle is 2,970 L/cycle. The SOPs developed are the Technology Operational SOP, maintenance SOP (Chlorine Tablet, Backwash and Sludge Disposal).